Training on Social Media Utilisation in Business Innovation for Legok Village Culinary MSMEs - Cynthia Sari Dewi; Melissa Indah Fianty; Fahmy Rinanda Saputri (Warta Pengabdian Andalas)
In the digital age, the role of social media in business innovation cannot be underestimated. Micro, Small, and Medium Enterprises (MSMEs) are crucial in driving economies, and their success significantly impacts local communities. However, the MSMEs Culinary in Legok faces tough competition from similar businesses that need help introducing their products or services. Therefore, with the training on social media for business innovation, MSMEs culinary in Legok Village can promote their products or services and reach a broader audience by producing social media content with relevant themes and concepts. This activity was conducted at Multimedia Nusantara University, Scientia Boulevard Gading Street, Curug Sangereng, Serpong, Tangerang Regency, Banten.